INTERAKSI IBA DAN IAA TERHADAP JUMLAH DAUN DAN BERAT KERING TANAMAN PISANG CAVENDISH (Musa acuminata) PERIODE SECONDARY HARDENING - Hilda Adina Rahmi; Nora Augustien; Nova Triani (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2021)
One of the stages in tissue culture activities at the final stage is the acclimatization stage. Leaves are plant organs that are important in the formation of photosynthesis which will become energy to meet the needs of plant growth activities. The large number of leaves formed during the plant growth period has an influence on the formation of plant energy, one form of measuring plant development from plant biomass can be in the form of plant dry weight. Growth and development in plants is closely related to hormones. This study aimed to examine the interaction between PGR IAA and IBA on the growth of Cavendish banana (Musa acuminata) during the secondary hardening period. The research was conducted at the Screen House of the Faculty of Agriculture, UPN “Veteran”, East Java. The research method used was a factorial completely randomized design. There are two factors consisting of 16 treatments. The first factor is the growth regulator IBA with a concentration consisting of I1 (Control); I2 (0.5 mg/l); I3(1.0 mg/l); I4 (1.5 mg/l). The second factor is the concentration of IAA growth regulators consisted of I1 (Control); I2 (0.5 mg/l); I3(1.0 mg/l); I4 (1.5 mg/l). The effect of treatment using the BNT test level 5%. The results showed an interaction between the concentration levels of IBA and IAA number of leaves and dry weight of Cavendish bananas in the secondary setting period. Treatment I4A4 (1.5 ml IBA + 1.5 ml IAA) gave the best results on the number of plant leaves by 75.8% at the end of the observation. Treatment I4A3 (1.5 ml IBA + 1.0 ml IAA) gave the heaviest yield on plant weight of 43.1% at the end of the observation.